EVALUATION OF THE POND SEDIMENT QUALITY OF BLACK TIGER SHRIMP (Penaeus monodon) CULTIVATION IN MARGASARI VILLAGE LABUHAN MARINGGAI DISTRICT LAMPUNG TIMUR REGENCY - Nugra, Balan; Wardiyanto, Wardiyanto; Supono, Supono (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2019)
Margasari aquaculture area in Labuhan Maringgai District of East Lampung Regency is applying the system of black tiger shrimp (Penaeus monodon) extensively. The decrease in the number of shrimp production in Margasari Village is suspected as a result of sediment degradation in the pond area. This study was aimed to evaluate the quality of sediment in the pond area for the cultivation of black tiger shrimp. The samples were collected for 4 weeks at 3 ponds, data were analyzed qualitatively and quantitatively. The results showed the location of ponds of 1 belongs to the suitability of the highly suitable (S1) for cultivation activities. The location of ponds of 2 and 3 belong to the moderately suitable (S2) for the cultivation of black tiger shrimp, and requiring more treatment for pH, C-Organic, nitrogen, potassium.